Calculus of Variations, Optimal Control, and Mathematical Biology A Themed Issue Dedicated to Professor Delfim F. M. Torres on the Occasion of His 50th Birthday (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint is dedicated to Professor Delfim F. M. Torres for his 50th birthday. Professor Delfim F. M. Torres is a recognized researcher, particularly in the calculus of variations, optimal control, and mathematical biology. In this reprint, several studies in his research fields are presented.